2021
DOI: 10.3390/genes12071049
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome-Wide Association Study of Blood Cell Traits in African Ancestry and Hispanic/Latino Populations

Abstract: Background: Thousands of genetic variants have been associated with hematological traits, though target genes remain unknown at most loci. Moreover, limited analyses have been conducted in African ancestry and Hispanic/Latino populations; hematological trait associated variants more common in these populations have likely been missed. Methods: To derive gene expression prediction models, we used ancestry-stratified datasets from the Multi-Ethnic Study of Atherosclerosis (MESA, including n = 229 African America… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 70 publications
(110 reference statements)
1
6
0
Order By: Relevance
“…Our third major finding was that TWAS models trained in the ancestrally diverse GALA II/SAGE population identified significantly more trait-associated genes than models trained in GTEx and MESA when applied to GWAS results from the multi-ancestry PAGE study. GALA II/SAGE TWAS models benefit from having more similar allele frequency profiles and more accurate modeling of linkage disequilibrium, which is consistent with previous observations 11 , 12 , 40 that ancestry-concordant models improve the power for gene discovery in TWASs. Furthermore, over 40% of significantly associated TWAS genes detected using GALA II/SAGE models were not available in GTEx.…”
Section: Discussionsupporting
confidence: 86%
“…Our third major finding was that TWAS models trained in the ancestrally diverse GALA II/SAGE population identified significantly more trait-associated genes than models trained in GTEx and MESA when applied to GWAS results from the multi-ancestry PAGE study. GALA II/SAGE TWAS models benefit from having more similar allele frequency profiles and more accurate modeling of linkage disequilibrium, which is consistent with previous observations 11 , 12 , 40 that ancestry-concordant models improve the power for gene discovery in TWASs. Furthermore, over 40% of significantly associated TWAS genes detected using GALA II/SAGE models were not available in GTEx.…”
Section: Discussionsupporting
confidence: 86%
“…Next, we found a marked difference between the genetic architecture of neutrophil count in people of African vs. European ancestry [38]. Interestingly, tissue expression for BCTs has been found to vary between ancestries as well [73], further showing the importance of conducting GWAS in diverse populations to improve the understanding of BCT biology. We investigated some of the GCTA-COJO index SNPs in relation to a biological mechanism that could explain how allele variation might affect neutrophil count levels in people of African ancestry.…”
Section: Discussionmentioning
confidence: 99%
“…We applied the Bonferroni correction to adjust the reported P-values with n=23,000. To validate our TWAS results, we compared them to five independent TWAS studies: Lu and Gopalan et al 36 , Kachuri et al 31 , Tapia et al 82 , Rowland et al 84 , and Wen et al 83 We released our cis -molQTL prediction weights to the public, which can be found at the Data Availability section. To test the association between T/PWAS chi-square statistics and genes’ constraint scores: pLI 75 , LOEUF 76 , EDS 77 , RVIS 78 , and s het 79 , we used linear regression adjusted for phenotype and study and reported one-sided P values.…”
Section: Methodsmentioning
confidence: 99%